2022
DOI: 10.3168/jds.2021-20661
|View full text |Cite
|
Sign up to set email alerts
|

Milking system and premilking routines have a strong effect on the microbial community in bulk tank milk

Abstract: In this study, we investigated the variation in the microbial community present in bulk tank milk samples and the potential effect of different farm management factors. Bulk tank milk samples were collected repeatedly over one year from 42 farms located in northern Sweden. Total and thermoresistant bacteria counts and 16S rRNA gene-based amplicon sequencing were used to characterize microbial community composition. The microbial community was in general heterogeneous both within and between different farms and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 31 publications
0
7
0
2
Order By: Relevance
“…For some farms, there were major shifts over time in milk microbiota which were not correlated with changes in management, indicating that other factors, e.g., the weather during the harvesting season, contributed to the observed differences [29]. Investigating the variation in the microbiota in bulk milk collected monthly on 42 dairy farms over one year, we found that the type of dairy farm (milking system) had a strong effect on the bulk milk microbiota, an effect likely associated with hygiene routines during the pre-milking and cleaning of the milking equipment [8]. The 18 farms used in the present study were selected from among those original 42 farms and an effect of milking system on bulk milk microbiota was also clear in the present study.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…For some farms, there were major shifts over time in milk microbiota which were not correlated with changes in management, indicating that other factors, e.g., the weather during the harvesting season, contributed to the observed differences [29]. Investigating the variation in the microbiota in bulk milk collected monthly on 42 dairy farms over one year, we found that the type of dairy farm (milking system) had a strong effect on the bulk milk microbiota, an effect likely associated with hygiene routines during the pre-milking and cleaning of the milking equipment [8]. The 18 farms used in the present study were selected from among those original 42 farms and an effect of milking system on bulk milk microbiota was also clear in the present study.…”
Section: Discussionmentioning
confidence: 82%
“…Stricter hygiene on farms, including pre-milking, udder-cleaning, and teat-disinfection routines, have likely contributed to reducing the total number of bacteria in bulk milk and therefore also the number of NSLAB in the milk, with consequences for the cheese maturation process. In a recent study, we explored farm-related factors contributing to the variation in the microbial community in bulk milk from different dairy farms [8]. The results revealed an effect of routines associated with teat preparation and cleaning of the milking equipment on bulk milk microbiota, with milk from farms using an automated milking system (AMS) having different microbial composition than milk from tie-stall farms.…”
Section: Introductionmentioning
confidence: 99%
“…Pseudomonas and Acinetobacter were the genera with the highest relative abundances in the bulk tank samples [37] and pasteurized milk [2]. A recent Swedish study identified Pseudomonas, Streptococcus, Acinetobacter, and Staphylococcus as the top abundant bacterial genera in tank milk [38]. The variation in bacterial community composition in raw milk could be attributed to the core microbiota present in pasteurized milk.…”
Section: The Bacterial Community Composition In Pasteurized Milk Duri...mentioning
confidence: 91%
“…Studien genomfördes i Västerbotten och omfattade 18 mjölkgårdar. Dessa hade tidigare deltagit i en mer omfattande studie (Priyashantha et al, 2021;Sun et al, 2022), vilket innebar att vi redan hade bakgrundsinformation om produktionen på gårdarna. En inledande intervju gjordes för att uppdatera informationen avseende rutiner, utfodring och mjölkning.…”
Section: Materials Och Metoderunclassified
“…I ett tidigare projekt har vi studerat vilka faktorer på gården som påverkar tankmjölkens mikroflora (Sun et al, 2022). Studien visade att det fanns en skillnad i mikrofloran i tankmjölken kopplat till gårdarnas mjölkningssystem, där besättningar med automatisk mjölkning hade en annorlunda mikroflora jämfört med uppbundna besättningar.…”
Section: Introduktionunclassified